2022
DOI: 10.1097/gox.0000000000004484
|View full text |Cite
|
Sign up to set email alerts
|

Bipedicled SIEA Flap with Deep Inferior Epigastric Artery and Vein Grafts for Breast Reconstruction

Abstract: Summary: A superficial inferior epigastric artery (SIEA) flap can be an alternative to a deep inferior epigastric artery perforator (DIEAP) flap in cases where SIEAs are relatively well developed. Although an SIEA flap is less invasive than a DIEAP flap, the pedicles of the former are anatomically shorter, making it more difficult to choose recipient vessels when bilateral SIEAs are necessary. A 45-year-old female diagnosed with cancer of the left breast underwent mastectomy (specimen weight: 750 g) and immedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Tessler et al first demonstrated the use of stacked lateral thigh perforator flaps in eight patients (16 flaps) with 100 percent flap survival ( 33 ). Recently, a case report from Nakamura et al has even reported using a bipedicled stacked SIEA flap with deep inferior epigastric artery and vein grafts to extend one of the pedicles, giving further flexibility in using bilateral SIEA flaps for unilateral breast reconstruction ( 34 ).…”
Section: Nuances and Applications Of Stacked/conjoined Flapsmentioning
confidence: 99%
“…Tessler et al first demonstrated the use of stacked lateral thigh perforator flaps in eight patients (16 flaps) with 100 percent flap survival ( 33 ). Recently, a case report from Nakamura et al has even reported using a bipedicled stacked SIEA flap with deep inferior epigastric artery and vein grafts to extend one of the pedicles, giving further flexibility in using bilateral SIEA flaps for unilateral breast reconstruction ( 34 ).…”
Section: Nuances and Applications Of Stacked/conjoined Flapsmentioning
confidence: 99%